Applicability of risk compensation to the relationship between health behaviors and COVID-19 vaccination among inpatients in Taizhou, China. - Chen, Liguang; Tung, Tao-Hsin; Zhang, Xinxin; Wang, Gang (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: Based on the risk compensation theory, this study was designed to investigate the relationship between health behaviors of inpatients and COVID-19 vaccination during the epidemic with regard to the Omicron variant of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Taizhou, China. Subject and methods: We conducted an online self-administered survey with a group of inpatients in a grade III, class A hospital in Taizhou, China, from February 27, 2022, to March 8, 2022. A total of 562 complete questionnaires were collected, and 18 questionnaires completed in under 180 seconds were rejected, leaving a total of 544 (96.8%) valid questionnaires collected. The participants who had received a COVID-19 vaccine were asked to describe the differences in their health behaviors before and after the vaccination, and the data were analyzed using SPSS Statistics version 22.0 software. Results: There were significant differences in the percentage of individuals wearing masks (97.2% and 78.9%, P < 0.001) and the percentage of hand washing after taking off the mask (89.1% and 63.2%, P < 0.001) between the inoculated group and the uninoculated group; however, there were no significant differences in other health behaviors. The participants showed better health behaviors (handwashing and wearing a mask) after the vaccination than prior to it. Conclusions: Our findings suggest that the Peltzman effect did not increase risk behaviors during the Omicron epidemic. There was no reduction in health behaviors among inpatients after the COVID-19 vaccine, which may have even improved their health behaviors.